Preclinical Evaluation of Carfilzomib for Infant KMT2A-Rearranged Acute Lymphoblastic Leukemia. - Cheung, Laurence; de Kraa, Rebecca; Oommen, Joyce; Chua, Grace-Alyssa; Singh, Sajla; Hughes, Anastasia M; Ferrari, Emanuela; Ford, Jette; Chiu, Sung K; Stam, Ronald W; Kees, Ursula R; Malinge, Sébastien; et al. (2021)
Background: Infants with KMT2A-rearranged B-cell precursor acute lymphoblastic leukemia (ALL) have poor outcomes. There is an urgent need to identify novel agents to improve survival. Proteasome inhibition has emerged as a promising therapeutic strategy for several hematological malignancies. The aim of this study was to determine the preclinical efficacy of the selective proteasome inhibitor carfilzomib, for infants with KMT2A-rearranged ALL.